2017
DOI: 10.1177/0333102417728244
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and critical appraisal of gene polymorphism association studies in medication-overuse headache

Abstract: Purpose of review Medication-overuse headache is a secondary chronic headache disorder, evolving from an episodic primary headache type, caused by the frequent and excessive use of headache symptomatic drugs. While gene polymorphisms have been deeply investigated as susceptibility factors for migraine, little attention has been paid to medication-overuse headache genetics. In the present study we conducted a systematic review to identify, appraise and summarize the current findings of gene polymorphism associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 54 publications
0
17
0
3
Order By: Relevance
“…In a recent systematic review, Cargnin et al described candidate polymorphic variants in genes of the dopaminergic gene system (DRD4, DRD2, SLC6A3), and genes related to drug-dependence pathways (WSF1, BDNF, ACE, HDAC3). The authors concluded that these traits are potential risk factors for MOH susceptibility or determinants of monthly drug consumption [ 100 107 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In a recent systematic review, Cargnin et al described candidate polymorphic variants in genes of the dopaminergic gene system (DRD4, DRD2, SLC6A3), and genes related to drug-dependence pathways (WSF1, BDNF, ACE, HDAC3). The authors concluded that these traits are potential risk factors for MOH susceptibility or determinants of monthly drug consumption [ 100 107 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The development of MOH is associated with a background of a primary headache disorder, frequent intake of analgesics, increasing frequency of headaches, psychological and personality traits, and genetic predisposition 24,25 . Genes involved in pain, drug‐dependence, metabolic, serotonergic, and dopaminergic pathways have been linked to MOH 24‐28 . Interestingly, regular use of analgesics for a non‐headache indication is associated with the development of chronic headache, specifically in migraine patients 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies, however, indicate differences in the brains of patients with migraine and with MOH, including reductions in the grey matter volume in areas associated with pain processing ( 41 , 42 ), and functional reactivity and resting state connectivity of brain regions involved in pain processing and modulation as well as cognitive and affective processing of pain ( 43 ). Furthermore, genetic studies have suggested particular gene polymorphisms may increase the risk of patients developing MOH, including genes involved in dopaminergic and serotonergic pathways ( 44 ). These studies augment findings that the serotonin (5-HT) system is altered in MOH, with decreased 5-HT levels ( 45 ) and increased levels of 5-HT receptors ( 46 ) in patients with MOH.…”
Section: Discussionmentioning
confidence: 99%